EKSISTENSI PENGADILAN AGAMA PASCA PENYATUAN SATU ATAP (INDEPENDENSI DAN PENGEMBANGANNYA) - Mardi Candra (Universitas Muhammadiyah Malang, 2020)
(The abstract should not exceed 250 words. It should briefly summarize the essence of the paper and address the following areas without using specific subsection titles.): Objective: Briefly state the problem or issue addressed, in language accessible to a general scientific audience. Technology or Method: Briefly summarize the technological innovation or method used to address the problem. Results: Provide a brief summary of the results and findings. Conclusions: Give brief concluding remarks on your outcomes. Clinical Impact: Comment on the translational aspect of the work presented in the paper and its potential clinical impact. Detailed discussion of these aspects should be provided in the main body of the paper.